Growth Identification and Facilitation : The Role of the State in the Dynamics of Structural Change - Lin, Justin; Monga, Celestin (2012)
The historical record indicates that in all successful economies, the state has always played an important role in facilitating structural change and helping the private sector sustain it across time. This paper puts forward a new approach to help policymakers in developing countries identify those industries that may hold latent comparative advantage and recommends ways of removing binding constraints to facilitate private firms' entry into those industries. Two types of government interventions are distinguished, first are policies that facilitate structural change by overcoming information and coordination and externality issues, which are intrinsic to industrial upgrading and diversification; and second policies aimed at protecting some selected firms and industries that defy the comparative advantage determined by the existing endowment structure.